Design of Flapping Wing Mini Air Vehicle with Crank-Rocker Mechanism - Sipahi, Muhammed Alpaslan; Yilmaz, Abdurrahman; Kaya, Alican; Cil, Ata Ertug; Demircali, Ali Anil; Uvet, Huseyin (IEEE, 2019)
In this study, design of flapping wing mini air vehicle (FWMAV) and comparison of wing designs which are chosen with respect to mass parameters are investigated. Wing shape and aspect ratio (AR) affects are observed by using finite element method (FEM) in COMSOL (R). To examine thrust of our mechanism for one cycle flapping motion, FEM and empirical formulations are used. Calculation steps of a relationship between wing design parameters and mass of the system are presented. These relations are originated from bird's nature. The flapping wing motion is achieved via a crank-rocker mechanism that generates harmonic flap function. These simulations are made for three different wings whose wing area, wing span and flapping frequency are same. We observed the effect of wing geometry over lift force by comparing wing design. The result of empirical calculation and simulation values show that there is a payload loss of %7 via empirical formulations.
Keywords: Flapping Wing; FWMAV; Microrobots; Biomimetic; Automation & Control Systems; Engineering